Memorandum of Understanding between the International Network for the Availability of Scientific Publications and Ayesha Abed Library, Brac University (2012) - Ayesha Abed Library, Brac University (Brac University and the International Network for the Availability of Scientific Publications, 2019)
The agreement made between The lntornational Network for the Availability of Scientific Publications and Ayesha Abed Library, BRAC University for using open source content management system Drupal to build library websites.